#TITLE_ALTERNATIVE# - GUNADI (NIM 22290003), BAMBANG
The key success in the reservoir management practice is to have a good characterization or description of the reservoir. The reservoirs are, in some degree, heterogenous. The actual value of properties are known only in wells. The problem of reservoir characterization is to estimate the reservoir properties values between the wells drilled, and the lateral boundaries. One approach to characterize a reservoir is the use of stochasti9 approach. Estimation of reservoir properties using stochastic approach needs semivariogram representing the spatial correlation of the properties. For the limited data available, it is difficult to derive the proper semivariogram model. To overcome this problem, a trial and error procedure is used.